Peran Investor Asing dalam Sektor Jasa Konstruksi di Indonesia - Purwanto, Purwanto (Pusat Penelitian Ekonomi-LIPI, 2010)
The existence of construction sector in the structure of the national economy can be seen by their role in producing physical output that supports the smoothness of the economic activities. The development of the construction sector depends on the availability of the fund and project development provided by the government. Therefore, the involvement of private sector on the construction must be increased to support the limit of government budget. Nevertheless, the increase of foreign construction companies in Indonesia raises the concern of the emergence of their domination in national construction sector. This article aims to analyze the role of the construction sector in the national economy and to explain the domination of the foreign investors in Indonesia's construction sector. This article suggests that the involvement of foreign private enterprise must be followed by an increase on the competitiveness of domestic enterprise in the construction sector. Furthermore, the increase of financial capacity, company's capacity, technological command, and quality of human resources are some indicators that need to be improved. On the other hand, fiscal stimulus is an alternative solution for increasing the activity of the construction sector especially for their benefit for creating more job opportunities. With the existence of the increase in local competitiveness, foreign domination in construction sector can be minimized and precisely open the opportunity for the involvement of the local contractors in large scale construction projects in Indonesia.